1976
DOI: 10.1084/jem.143.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous oncornaviral gene expression in adult and fetal mice: quantitative, histologic, and physiologic studies of the major viral glycorprotein, gp70.

Abstract: Endogenous expression of the murine leukemia virus (MuLV) genome has been studied in a number of strains of mice. Expression of the major envelope glycoprotein, gp70, is restricted to certain anatomical sites and cell types, prominent among which are lymphoid and epithelial cells. On a quantitative basis, the major site of gp70 expression is the male genital tract. During development, gp70 first appears in the hematopoietic liver of 14-day-old embryos and by day 18, it is already expressed at anatomical sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(69 citation statements)
references
References 29 publications
2
67
0
Order By: Relevance
“…Expression of genes of the xenotropic viruses seems to occur in differentiating cells. The viral glycoprotein gp70 has been found in differentiating thymocytes (36,37), in the male genital tract, and in sperm (38). Hematopoietic cells (39), embryos and placenta (40), as well as regenerating liver cells (41) probably express these viruses or part of their genes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of genes of the xenotropic viruses seems to occur in differentiating cells. The viral glycoprotein gp70 has been found in differentiating thymocytes (36,37), in the male genital tract, and in sperm (38). Hematopoietic cells (39), embryos and placenta (40), as well as regenerating liver cells (41) probably express these viruses or part of their genes.…”
Section: Discussionmentioning
confidence: 99%
“…Presently there is no evidence that the lymphocyte membrane antigen(s) detected with the extensively absorbed anti-SLE antisera described here have any relationship to virus or cell surface determinants related to any viral genome (37)(38)(39)(40). Considerably more work will be necessary before such a possibility can be resolved.…”
Section: Resultsmentioning
confidence: 94%
“…No digestion of gp70, as determined by measuring the size of gp70 by sucrose density gradient analysis, was found in vitro after 1,2, and 3 hours of incubation at 37°C. In addition, the clearance rate of gp70 from tissue cage fluids 6.5 hours), which was determined following the injection of serum gp70 into the tissue cage, was comparable with the clearance rate of gp70 from sera (T1/2 5.5 hours) (20). We tested other biologic fluids for gp70 levels to exclude a peculiarity of our tissue cage model.…”
Section: Resultsmentioning
confidence: 99%
“…First, tissue cage fluids did not exhibit significant proteolytic activities for gp70. Second, kinetrics studies have shown that the disappearance rate of gp70 injected into tissue cages was not significantly different from its clearance rate in sera (20).…”
Section: -mentioning
confidence: 99%